Mother Camp has Arrived: an analysis of the Spanish translation of Esther Newton’s ethnographic text on drag queens in America - Villanueva-Jordán, Iván (2023)
This article contains an analysis of the Spanish translation of Mother Camp, Esther Newton’s ethnography, which was initially published in 1972. The 2016 translation by Belbel Bullejos and Uría constitutes a corpus that lends itself to an exploration of the limits of the translation of gender as a relational category. In the Spanish version of this ethnographic text, several equivalents proposed for identity categories point to incommensurability among various signifiers related to bodies, sexuality, and gendered life experiences. Moreover, different domesticating translation strategies adapted for Peninsular Spanish readers contribute to the Spanish translation reading like a fiction/non-fiction hybrid text. The selected strategies mask the temporally and geographically bound representation of sex/gender dissent and the experimental innovations of Newton’s ethnographic discourse.